2020
DOI: 10.1177/0269215520964950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kinesio taping on hemiplegic shoulder pain: A systematic review and meta-analysis of randomized controlled trials

Abstract: Objective: The aim of this study was to evaluate the effectiveness of kinesio taping for the management of hemiplegic shoulder pain. Data sources: MEDLINE, EMBASE, Web of Science, CENTRAL, CNKI, Wan Fang databases and the grey literature research were searched from inception to July 2020. Methods: We considered randomized controlled trials in English or Chinese that used kinesio taping for the treatment of hemiplegic shoulder pain. Two reviewers independently screened the articles, scored the methodological qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Suprascapular nerve blocks, with and without corticosteroids, increased passive range of motion 55 . A functional bandage reduced shoulder subluxation, improved upper limb motor function and activities of everyday life, and reduced pain when compared to placebo 56,57 .…”
Section: Painful Shouldermentioning
confidence: 97%
“…Suprascapular nerve blocks, with and without corticosteroids, increased passive range of motion 55 . A functional bandage reduced shoulder subluxation, improved upper limb motor function and activities of everyday life, and reduced pain when compared to placebo 56,57 .…”
Section: Painful Shouldermentioning
confidence: 97%
“…Korkmaz et al ( 52 ) found that the AGTD is strongly related to biceps tendinitis, which can lead to shoulder pain. Many studies have pointed out that transcutaneous nerve electrical stimulation (TENS) around shoulder ( 53 ), wearing of shoulder orthosis ( 54 ) and kinesiology taping ( 18 ) can significantly improve shoulder subluxation and shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Many treatments can be used to relieve shoulder pain after stroke. Traditional treatment methods include pills, electrical stimulation ( 17 ), kinesio taping ( 18 ), arm orthosis ( 19 ) to protect shoulder joint, closed injection to suppress immune response, shoulder training and other exercise therapies to promote functional recovery of upper limbs and shoulders, traditional Chinese medicine fumigation and acupuncture ( 20 ). Although most patients benefit from traditional treatment, the remaining the patients with persistent shoulder pain do not get relief after using traditional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed beneficial effects of KT have led to it becoming part of the daily treatment and rehabilitation programs of many sporting therapists ( Dolphin et al, 2021 ). It is proposed to activate the pain-suppressing system and release the compression on nociceptors to relieve the pain ( Montalvo et al, 2014 ; Deng et al, 2021 ). Additionally, KT is suggested to enhance lower-extremity muscle activity, strength, and tone, as well as dynamic stability ( Kim and Kim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%